Picturing royal charisma : kings and rulers in the Near East from 3000 BCE to 1700 CE : proceedings of an international workshop, the Mandel Scholion Interdisciplinary Research Center in the Humanities and Jewish Studies, The Hebrew University of Jerusalem, January 2015, Jerusalem - David, Arlette,; Milstein, Rachel,; Ornan, Tallay, (Archaeopress Archaeology, 2023)
This work assesses how Middle Eastern leaders manipulated visuals to advance their rule from around 4500 BC to the 19th century AD. In nine fascinating narratives, it showcases the dynamics of long-lasting Middle Eastern traditions, dealing with the visualisation of those who stood at the head of the social order.